Cerebrospinal fluid ctDNA as a diagnostic and prognostic tool in gliomas: a systematic review and meta-analysis - Pérez-Alfayate, Rebeca; Paz-Cabezas, Mateo; Pérez-Segura, Pedro; Sanchez del Hoyo, Rafael; Cabezas-Camarero, Santiago (Frontiers in Oncology, 2025)
BackgroundLiquid biopsy using circulating tumor DNA (ctDNA) has emerged as a promising tool for molecular characterization and monitoring in gliomas. This systematic review and meta-analysis evaluated the diagnostic and prognostic value of ctDNA in cerebrospinal fluid (CSF), compared to plasma, as well as factors influencing its detection.MethodsWe systematically reviewed studies published between 2015 and 2025 reporting on ctDNA detection in CSF from adult glioma patients. Pooled analyses compared detection rates between CSF and plasma, CSF collection routes, assay types (targeted vs. bespoke), and IDH mutation status. Molecular concordance with tumor tissue and clinical correlations were also assessed.ResultsTwelve studies comprising 388 patients with WHO grade II–IV gliomas were included. ctDNA detection in CSF was achieved in 82% of patients, compared with only 16% in plasma. Tumor–CSF molecular concordance was 90% (95% CI 86–93). Detection was significantly higher in CSF than in plasma (OR 0.05, 95% CI 0.01–0.24). No significant differences were observed between IDH-wildtype and IDH-mutant gliomas (OR 0.72, 95% CI 0.26–2.02) or between intracranial and lumbar CSF collection techniques (p > 0.9).ConclusionsCSF outperforms plasma for ctDNA-based molecular profiling in gliomas, offering both diagnostic and prognostic applications. Detection is numerically higher in IDH-wildtype gliomas, underscoring its potential role as a biomarker in this subgroup. While no significant differences were observed between collection routes in the pooled analysis, single-study evidence suggests a possible advantage of intracranial sampling, which requires further prospective evaluation. Its integration into clinical workflows may aid in cases where tissue biopsy is not feasible. Standardized methodologies and prospective multicenter validation are needed to enable routine clinical implementation.